Охоронні розкопки черняхівського могильника Городок - Нікітін, В.І. (Археологія, 2013)
Публікуються нові матеріали могильника черняхівського часу, частково зруйнованого господарськими роботами. Публикуются материалы исследования частично разрушенного могильника черняховского времени — iV в., расположенного на мысе при впадении р. Чичиклея в Южный Буг у с. Новый Городок Веселиновского р-на Николаевской обл. Выявлено 11 погребений с трупоположением и сопутствующим инвентарем. На фоне предыдущих раскопок на плато, где преобладали сожжения в ямах или урнах, на склоне выявлены только трупоположения, что ставит проблему причин различий в погребальном обряде. Published are the materials from the research of the 4th c. partly destroyed chernyakhivska culture period burial ground situated on cape in the place where the chychykleya River falls into the Southern Buh River near novyi horodok village in Veselynivka Region of Mykolayiv oblast. 11 graves with inhumations and accompanying inventory were revealed. at a background of previous excavations at the upland where cremations in pits and urns prevailed, inhumations exclusively found at the slopes raise the problem of differences in funeral rites.